Immune Response and Performance of Broiler Chicks Fed Protexin and Propionic Acid - Khosravi, Ali; Boldaji, Fathollah; Dastar, Behrouz; Hasani, Saeed (International Journal of Poultry Science, 2010)
This study was conducted to evaluate the effects of dietary protexin, propionic acid and a blend of protexin and propionic acid on the immune response and the performance of broiler chicks. In a completely randomized design, three hundred and twenty broiler chicks were divided into 4 groups (each group consisting of 16 unsexed 1-d-old chicks) and reared on floor pens for 42 days. Dietary treatments consisted of a control diet without any additives, the control diet + 0.1 g/kg protexin, the control diet +2 g/kg propionic acid, and the control diet + 0.1 g/kg protexin + 2 g/kg propionic acid. On the 42 day, body weight gain and feed intake of chicks were calculated. On the same day, one male chick from each pen, which was the nearest to mean weight, was bled to determine blood parameters. Feed conversion ratio for birds fed a diet of propionic acid and a protexin + propionic acid differed (p <0.05) from control birds. Although body weight gain was numerically higher in the birds fed feed additives than the control diet, body weight gain for these birds did not differ (p>0.05) from control birds. There were no significant differences for feed intake and blood parameters among the dietary treatments. In conclusion, based on the results of the experiment, propionic acid and protexin have the potential to be used as feed additives in broiler diets.